Penfluridol as a Candidate of Drug Repurposing for Anticancer Agent - Nguyen Minh Tuan; Chang Hoon Lee (Molecules, 2019)
Penfluridol has robust antipsychotic efficacy and is a first-generation diphenylbutylpiperidine. Its effects last for several days after a single oral dose and it can be administered once a week to provide better compliance and symptom control. Recently; strong antitumour effects for penfluridol were discovered in various cancer cell lines; such as breast; pancreatic; glioblastoma; and lung cancer cells via several distinct mechanisms. Therefore; penfluridol has drawn much attention as a potentially novel anti-tumour agent. In addition; the anti-cancer effects of penfluridol have been demonstrated in vivo: results showed slight changes in the volume and weight of organs at doses tested in animals. This paper outlines the potential for penfluridol to be developed as a next-generation anticancer drug.